Distribution and association of factors influencing emerging maize lethal necrosis disease epidemics in Southern Ethiopia - Habtamu Terefe; Getachew Gudero (Cogent Food & Agriculture, 2019)
Maize lethal necrosis (MLN) disease has emerged as a great threat of maize production in Ethiopia. Thus, field surveys were conducted to determine the spatial distribution and association of MLN disease with biophysical factors in Southern Ethiopia, during 2016 and 2017 main cropping seasons. A total of 240 maize fields were inspected across seven districts in the 2 years. Results showed that MLN disease was 100% prevalent in maize fields though the level of importance varied among districts. Arbaminch, Mihirab Arbaya, Bonkie, Derashie, Konso and Burjdi districts lowered disease severity by 1.46%, 4.13%, 11.38%, 13.40%, 9.24% and 30.82% when compared with Demba Gofa district, respectively. Also, severe weed and insect infestations were evident in the assessed farms. The association of disease severity with biophysical factors was assessed using a logistic regression model. District, NPS fertilization, cropping system, insect and weed infestation and insecticide spray frequency were significantly associated with disease severity in the multiple reduced variable model. High (>50%) disease severity had about four, three, and two times high probability of relationship with Demba Gofa, Arbaminch, and Mihirab Arbaya, Konso, Derashie and Bonkie districts, respectively. Similarly, 0 to 50 kg ha−1 NPS fertilization, sole cropping, high insect and weed infestation and none to once insecticide spray showed a high probability of association with disease severity. The results indicated that MLN disease is highly prevalent, severe and important in Southern Ethiopia. Therefore, weeding, insect vector control, NPS fertilization, intercropping, along with other agronomic practices, are recommended in the study areas and other related agro-ecologies.